Towards a unified model of neutrino-nucleus reactions for neutrino oscillation experiments. (10th April 2017) - Nakamura, S X; Kamano, H; Hayato, Y; Hirai, M; Horiuchi, W; Kumano, S; Murata, T; Saito, K; Sakuda, M; Sato, T; Suzuki, Y
Abstract: A precise description of neutrino-nucleus reactions will play a key role in addressing fundamental questions such as the leptonic CP violation and the neutrino mass hierarchy through analyzing data from next-generation neutrino oscillation experiments. The neutrino energy relevant to the neutrino-nucleus reactions spans a broad range and, accordingly, the dominant reaction mechanism varies across the energy region from quasi-elastic scattering through nucleon resonance excitations to deep inelastic scattering. This corresponds to transitions of the effective degree of freedom for theoretical description from nucleons through meson-baryon to quarks. The main purpose of this review is to report our recent efforts towards a unified description of the neutrino-nucleus reactions over the wide energy range; recent overall progress in the field is also sketched. Starting with an overview of the current status of neutrino-nucleus scattering experiments, we formulate the cross section to be commonly used for the reactions over all the energy regions. A description of the neutrino-nucleon reactions follows and, in particular, a dynamical coupled-channels model for meson productions in and beyond the Δ (1232) region is discussed in detail. We then discuss the neutrino-nucleus reactions, putting emphasis on our theoretical approaches. We start the discussion with electroweak processes in few-nucleon systems studied with the correlated Gaussian method. Then we describe quasi-elastic scattering with nuclear spectral functions, and meson productions with a Δ -hole model. Nuclear modifications of the parton distribution functions determined through a global analysis are also discussed. Finally, we discuss issues to be addressed for future developments.